SYNTHESIS AND CRYSTAL STRUCTURE ANALYSIS OF A NEW CHALCONE DERIVATIVE OF APOCYNIN - Yanko Moreno (Journal of the Chilean Chemical Society, 2020)
In the present report we present the synthesis and structural analysis of a chalcone derivative of Apocynin, 1-(4-hydroxy-3-methoxyphenyl)-3-(4-nitrophenyl)-2-propenone.The most characteristic feature of its molecular structure is its near-planarity, allowing molecules to be stacked in columns, at graphite intermolecular distances to each other and connected by a large variety of weak intermolecular interactions.The molecule presents structural analogies to related ones with significant pharmacological properties (e.g., Apocynin).